Prevalence of Age-Related Malocclusion and Dental Anomalies in the Kosovo Region: A Retrospective Analysis - Selmani, Mimoza; Bukleta, Manushaqe Selmani (European Journal of General Dentistry, 2025)
The objective of this study was to assess the association between age and various types of dental malocclusion and anomalies.This retrospective cross-sectional study was conducted on 617 patients from Kosovo visiting orthodontic specialty clinics in Pristina, Kosovo between 2017 and 2023. Patients were divided into two age groups: under 18 years and 18 years or older. Dental anomalies (hypodontia, impaction, ectopic eruption, midline diastema), occlusal relationships (Angle's classification), malocclusion characteristics, and anterior/posterior crowding were assessed and their associations with age were evaluated. Inclusion criteria were complete dental records with no history of orthodontic treatment, no significant medical or dental conditions, and absence of extensive restorations affecting anomaly detection. Patients with maxillofacial trauma, oral pathologies, or syndromic diagnoses were excluded. Data were analyzed with IBM SPSS software version 16.0. Descriptive statistics and Chi-square tests with Bonferroni correction were applied to assess the association between dental anomalies and malocclusion classes. A p-value of <0.05 was considered statistically significant.Significant associations were observed between age and sagittal plane classification (p = 0.014), upper midline deviation (p = 0.037), posterior crossbite (p = 0.003), and open bite (p = 0.001). Among dental anomalies, hypodontia (p = 0.001), impaction (p = 0.004), and midline diastema (p = 0.001) were observed for their associations with age. No significant association was found with ectopic eruption, deep bite, anterior crossbite, and crowding.Age significantly influences specific malocclusion patterns and dental anomalies, particularly in sagittal relationships and tooth agenesis. These results emphasize the need for age-specific diagnosis and assessment and early intervention in orthodontic care.
Keywords: malocclusion; midline deviations; crossbite; open bite; hypodontia; impaction